2014
DOI: 10.1371/journal.pone.0108783
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variation of a Defensive Symbiosis in the Bugula neritina (Bryozoa) Sibling Species Complex

Abstract: Mutualistic relationships are beneficial for both partners and are often studied within a single environment. However, when the range of the partners is large, geographical differences in selective pressure may shift the relationship outcome from positive to negative. The marine bryozoan Bugula neritina is a colonial invertebrate common in temperate waters worldwide. It is the source of bioactive polyketide metabolites, the bryostatins. Evidence suggests that an uncultured vertically transmitted symbiont, “Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
0
27
1
Order By: Relevance
“…Endobugula sertula" (7), which is a pattern of distribution consistent with a vertical mode of symbiont transmission, where respective populations have been genetically isolated since host divergence. However, we previously found evidence that horizontal transmission is likely also possible (19). We found that two sibling species of B. neritina, northern (N) and shallow (S), previously thought to be allopatrically distributed, actually coexist along the Western Atlantic.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Endobugula sertula" (7), which is a pattern of distribution consistent with a vertical mode of symbiont transmission, where respective populations have been genetically isolated since host divergence. However, we previously found evidence that horizontal transmission is likely also possible (19). We found that two sibling species of B. neritina, northern (N) and shallow (S), previously thought to be allopatrically distributed, actually coexist along the Western Atlantic.…”
Section: Discussionmentioning
confidence: 83%
“…Although "Ca. Endobugula sertula" has proven difficult to isolate and culture, the lack of extensive genome reduction suggests that a transient host-free existence may be possible, a plausible explanation for the symbiont acquisition by type N hosts found alongside symbiotic type S hosts at low latitudes (19) PCR amplicons observed PCR amplicons not observed…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent molecular evidence suggests that B. neritina consists of at least three genetically distinct types of colonies along the coasts of the USA [41,46] [27]. Type S colonies have an invasive behaviour, are globally distributed, including genetic confirmation of colonies from Galicia-in the north-eastern Atlantic [27], and are considered to have undergone widespread introduction as a fouling organism [74].…”
Section: Bugula Neritina Linnaeus 1758mentioning
confidence: 99%